PENGARUH STRES KERJA DAN AMBIGUITAS PERAN TERHADAP KINERJA PEGAWAI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI MEDIASI STUDI PADA DOSEN WANITA BERSTATUS MENIKAH DI POLITEKNIK NEGERI AMBON - Emilia Jean Latuihamallo; Conchita Valentina Latupapua; Agusthina Risambessy (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Human resources are the most important asset for an organization, because they are the main key that must be considered with all its needs indetermining the successful implementation of an organization's activities. Human resource management cannot be separated from employees whoare expected to perform as well as possible in order to achieve organizational goals. The variable used as intervening is OrganizationalCitizenship Behavior (OCB). The phenomenon that occurs at the Ambon State Polytechnic lies in female teaching staff (lecturers) who aremarried because the workload is increasingly being felt by several teaching staff who have been interviewed by researchers. Where it is difficultfor them to place themselves in several roles that they have to do, especially when they have to rush or have to meet deadlines, such as having towork on faculty accreditation in such a short time. This causes stress for teaching staff. Based on the phenomena presented at the researchlocation, there are several things that must be considered to improve performance. Therefore, the researcher intends to examine more deeplythe relationship between the four variables, namely; Job Stress, Role Ambiguity, Organizational Citizenship Behavior, Employee PerformanceThis aims to safeguard the company's important assets, namely human resources. Based on the PLS test results, it was found that the pathcoefficient value for this variable was 0.034 with a t-statistic value of 3,747 which was smaller than the standard value of 1.682 and a P-Valuevalue of 0.028<a significance level of 0.05. This shows that the variable Role Ambiguity has a positive and significant effect on EmployeePerformance through Organizational Citizenship Behavior, which also means that the sixth hypothesis (H6) 'Role Ambiguity on EmployeePerformance Through Organizational Citizenship Behavior is accepted. Employee Performance through Organizational Citizenship Behavior,which also means that the sixth hypothesis (H6) 'Role Ambiguity on Employee Performance Through Organizational Citizenship Behavior is accepted.